2022
DOI: 10.1002/cphc.202200645
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Au Formation on Au Substrates via High Voltage Electrolysis**

Abstract: Nanoporous Au (NPG) films have promising properties, making them suitable for various applications in (electro)catalysis or (bio)sensing. Tuning the structural properties, such as the pore size or the surface‐to‐volume ratio, often requires complex starting materials such as alloys, multiple synthesis steps, lengthy preparation procedures or a combination of these factors. Here we present an approach that circumvents these difficulties, enabling for a rapid and controlled preparation of NPG films starting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 62 publications
(168 reference statements)
2
25
0
Order By: Relevance
“…The corresponding charges are depicted in Figure b). Previous XPS measurements show that primarily Au 2 O 3 is formed under these conditions . Hence, the evaluated charge is directly proportional to the amount of Au 2 O 3 formed during HV electrolysis.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding charges are depicted in Figure b). Previous XPS measurements show that primarily Au 2 O 3 is formed under these conditions . Hence, the evaluated charge is directly proportional to the amount of Au 2 O 3 formed during HV electrolysis.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since Pt does not restructure during high voltage electrolysis, we use Au electrodes instead, which were shown to exhibit a voltage dependent Au oxide formation. 29,30 From our experiments, we will demonstrate that the current density is a better descriptor for the amount of Au oxide formed than the applied voltage.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated that the final structure of the NPG film depends on the method used to reduce the Au oxide, i. e., electrochemically or in the presence of H 2 O 2 [27] . For long electrolysis times, it is even possible to form a NPG film in situ in a single step [27] …”
Section: Introductionmentioning
confidence: 95%
“…The latter phenomenon refers to a plasma that forms in a gas sheath around the working electrode at high voltages [23–25] . In both cases, the voltages can reach several hundreds of volts and the current densities are in the range of 1 to 10 A cm −2 [26–28] . Advantages of this high voltage (current density) approach are that the preparation times are significantly shorter and only an (alkaline) electrolyte is required [27] .…”
Section: Introductionmentioning
confidence: 99%